VERMICULTURATION AND ITS DEVELOPMENT PROSPECTS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Reclamation products such as vermicompost and vermiculture are often used as feed additives and natural fertilizers. In addition, the most common methods and technologies for their production are relatively simple and inexpensive. This is a huge advantage over existing and currently used fertilizers and organic additives.